Are the curli proteins CsgE and CsgF intrinsically disordered?. Issue 1 (1st January 2016) - Green, Amanda; Pham, Nguyen; Osby, Krystle; Aram, Alexander; Claudius, Rochelle; Patray, Sharon; Jayasinghe, Sajith A.
Abstract: Curli are a type of proteinaceous cell surface filament produced by enteric bacteria such as Escherichia and Salmonella that facilitate cell adhesion and invasion, bio-film formation, and environmental persistence. Curli assembly involves 6 proteins encoded by the curli specific genes A, B, C, E, F, and G. Although CsgA is the major structural component of curli, CsgE, and CsgF, are thought to play important chaperone like functions in the assembly of CsgA into curli. Given that some proteins with chaperone like function have been observed to contain disordered regions, sequence analysis and circular dichroism spectroscopy was used to investigate the possibility that structures of CsgE and CsgF were also disordered. Sequence analysis based on charge and hydrophobicity, as well as using the disorder prediction software PONDR, indicates that both proteins have significant regions of disorder. The secondary structure and unfolding, of CsgE and CsgF, analyzed using circular dichroism spectroscopy suggests that both proteins lack a well defined and stable structure. These observations support the hypothesis that the curli assembly proteins CsgE and CsgF are disordered proteins containing intrinsically disordered regions.